2022
DOI: 10.3390/molecules27217180
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Content of Crackers and Bread Made with Purple and Blue Wheat Varieties

Abstract: Purple and blue wheats contain anthocyanins in the outer layers of the wheat kernel, and therefore purple and blue wholemeals can be a source of anthocyanins when developing processed cereal products. However, cereal processing is anticipated to cause significant anthocyanin losses. In this study, the anthocyanin content of crackers and bread made from one purple and three blue wholemeals was measured during processing and after baking. LC-MS/MS was used to confirm the presence of anthocyanins, and to tentativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Pigmented wheats with red, purple, blue, and black grains have attracted the attention of the food industry for their large content of flavonoid compounds and associated antioxidant activity [51]. In particular, colored whole grains are regarded as promising new functional foods due to their anthocyanin content located in outer layers (pericarp, aleurone, testa) of grains [52]. Numerous in vivo and in vitro studies have demonstrated the high antioxidative activity of anthocyanins [23,53] and their health effects, including cardio-protection, anti-diabetes, anti-obesity, anti-cancer, and anti-aging-affiliated pathology [51,52,54].…”
Section: Discussionmentioning
confidence: 99%
“…Pigmented wheats with red, purple, blue, and black grains have attracted the attention of the food industry for their large content of flavonoid compounds and associated antioxidant activity [51]. In particular, colored whole grains are regarded as promising new functional foods due to their anthocyanin content located in outer layers (pericarp, aleurone, testa) of grains [52]. Numerous in vivo and in vitro studies have demonstrated the high antioxidative activity of anthocyanins [23,53] and their health effects, including cardio-protection, anti-diabetes, anti-obesity, anti-cancer, and anti-aging-affiliated pathology [51,52,54].…”
Section: Discussionmentioning
confidence: 99%
“…The overall loss of TAC is greater in bread crust than that of bread crumb. Similarly, the anthocyanin concentration dramatically dropped after mixing and baking of purple and blue wheat bread doughs, but not after the fermentation or proofing steps [ 39 ]. Although the anthocyanin loss during baking cannot be completely prevented, it can be slowed down or controlled by altering the variables of the bread-making process.…”
Section: Purple Wheat Productsmentioning
confidence: 99%
“…Although the anthocyanin loss during baking cannot be completely prevented, it can be slowed down or controlled by altering the variables of the bread-making process. This may include using high-temperature, short-time baking processes, as well as a dough making process at a low pH [ 39 , 40 ]. For example, the fermentation of purple wheat with Lactiplantibacillus plantarum No.…”
Section: Purple Wheat Productsmentioning
confidence: 99%
See 2 more Smart Citations